High resolution climate and water cycle records in Antarctic ice cores with a focus on deglaciations - Grisart, Antoine (HAL CCSD, 2023)
Ice cores from the polar ice caps are valuable climate archives that have allowed us to document the past climate and environment. The EPICA Dome C (EDC) core in Antarctica was drilled to a depth of 3,189 m, which corresponds to an age of 800,000 years. This core located on the Antarctic Plateau is currently the longest continuous glacial archive providing high resolution stable isotope records of water and gas trapped in the ice to document past climate.This thesis focuses on the study of high frequency variability from high resolution sample measurements on the EDC core. In particular, we focus on the variability of the atmospheric hydrological cycle and climate during deglaciation.This thesis has consisted of extensive analytical work. First, from high resolution (11 cm) measurements of water isotopic composition on the EDC core, we concluded that the multi-centennial variability is lower during warm periods, called interglacials, than during cold periods, called glaciations. In addition, this data set allowed us to quantify the evolution of the diffusion length along the EDC core and to study how the diffusion in the ice attenuates the climate signal for the deepest part of the core.In a second step, I made measurements of δ15N of N2, δ18O of O2, δO2/N2 in the air trapped in the ice at a time resolution of 200-300 years over the different deglaciations. These data allow us to better date the ice core and study the evolution of the low-latitude hydrological cycle (δ18O of O2). I combined these data with other 17O - exess measurements that I made every 55 cm (50-300 year resolution) and d-excess data over the same time periods. The d-excess and the 17O - exess are tracers of the climatic conditions of the evaporation sources. By synthesizing these deglaciation data, we have described the sequences of events during orbital forcing-driven warming. In particular, we have highlighted a millennial variability that occurs during deglaciations at temperate latitudes but does not affect the Antarctic climate. There is ...